Comparative study on growth performance between Vietnam koi and Thai koi in mini ponds - Ahmed, GU; Upala, SR; Hasan, MT; Hasan, NA (Journal of the Bangladesh Agricultural University, 2016)
An experiment was carried out to determine the comparative growth study of Vietnam koi (Anabus testudineus) and Thai koi (Anabus testudineus) for a period of 90 days in eight experimental ponds in the northern side of the Faculty of Fisheries, Bangladesh Agricultural University, Mymensingh. Four treatments were considered having two replicates. For Vietnam koi treatments were named VT1 and VT2 and for Thai koi were TT1 and TT2. All the fish were of same age group having mean body weight of 0.30 g. Feeding frequency in all the treatments were two times a day. Fish were fed quality fish feed at a rate of 60% of their body weight for the first thirty days that was gradually reduced to 25% for the next thirty days and 10% till the termination of the experiment. The mean value of water temperature were 29.78 in VT1, 30.42 in VT2, 30.50 in TT1 and 29.99°C in TT2, dissolved oxygen were 7.21, 7.42 , 7.14 and 7.34 mg/l in VT1, VT2, TT1 and TT2, respectively, mean pH values were 7.42 in VT1, 7.29 in VT2, 7.50 in TT1 and 7.45 in TT2, ammonia were 0.21, 0.24, 0.28 and 0.23 mg/l in VT1, VT2, TT1 and TT2 , respectively and alkalinity were 200.00, 205.00, 210.00 and 205.00 ppm in VT1, VT2, TT1 and TT2 , respectively. The result of the present study showed that the best weight gain of 80.00 g was observed in VT1 after 90 days of culture period. Average weight gain (g) were 0.83, 0.88, 0.51 and 0.61; SGR (per day) were 3.93, 3.95, 3.65 and 3.71%; FCR were 1.50, 1.67, 1.70 and 1.90; survival rate were 78.50, 76.50, 90.00 and 82.00% and fish production were 7,839, 15,923, 5,519 and 11,820 kg/ha/3 months in VT1, VT2, TT1 and TT2, respectively. Growth of both the species was higher in lower stocking densities, whereas, production was increased in higher stocking densities. The present research findings suggested that Vietnam koi has high growth potential in comparison to Thai koi under mini pond culture condition. J. Bangladesh Agril. Univ. 12(2): 405-409, December 2014